Thermionic Vacuum Arc-A Versatile Technology for Thin Film Deposition and Its Applications; Coatings; Vol. 10, iss. 3 - Vladoiu R. Rodica; Tichy M. Milan; Mandes A. Aurelia; Dinca V. Virginia; Kudrn P. Pavel (2020, 2020)
Title screen